2020
DOI: 10.3390/ijerph17051563
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical, Mineralogical and Morphological Characterisation of Road Dust and Associated Health Risks

Abstract: Road dust resuspension, especially the particulate matter fraction below 10 µm (PM10), is one of the main air quality management challenges in Europe. Road dust samples were collected from representative streets (suburban and urban) of the city of Viana do Castelo, Portugal. PM10 emission factors (mg veh−1 km−1) ranging from 49 (asphalt) to 330 (cobble stone) were estimated by means of the United Stated Environmental Protection Agency method. Two road dust fractions (<0.074 mm and from 0.0074 to 1 mm) were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…The mean concentrations of Zn (1287 mg/kg) and Pb (762 mg/kg) in 2018 decreased by more than 60% compared to those in 2008, however, these values obtained after ceasing the IZS activities 12 years were still 14 and 26 times higher than the soil background values in Guizhou Province. Studies have shown that the anthropogenic enrichment of zinc and lead in urban samples has reached a medium level, indicating the contribution of traffic emissions [39]. For this study area, the excess accumulation of lead and zinc in dust is mainly attributed to industrial activities.…”
Section: Concentrations Of Heavy Metal(loid)s In Ground Dustmentioning
confidence: 72%
“…The mean concentrations of Zn (1287 mg/kg) and Pb (762 mg/kg) in 2018 decreased by more than 60% compared to those in 2008, however, these values obtained after ceasing the IZS activities 12 years were still 14 and 26 times higher than the soil background values in Guizhou Province. Studies have shown that the anthropogenic enrichment of zinc and lead in urban samples has reached a medium level, indicating the contribution of traffic emissions [39]. For this study area, the excess accumulation of lead and zinc in dust is mainly attributed to industrial activities.…”
Section: Concentrations Of Heavy Metal(loid)s In Ground Dustmentioning
confidence: 72%
“…A higher silica content may expose the community to serious health implications, such as damaged lung tissue [ 20 ]. Its higher concentration in road dust may be associated with its hardness, which makes it difficult to undergo physical weathering [ 31 ]. Additionally, the dominance of quartz in road dust may also be linked to the geographical location of the study area, which falls under the Johannesburg dome, which is underlain with sedimentary rocks of the Witwatersrand and Venterdorp Supergroup.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account that road dust resuspension is a current air quality management challenge in Europe, a study conducted in Viana do Castelo (Portugal) focused on this issue and characterized road dust samples collected in suburban and urban streets, defined PM 10 emissions factors for different road types and identified the main anthropogenic contributions to them [ 7 ]. Estimated PM 10 emission factors ranged from 49 mg veh −1 km −1 (asphalt) to 330 mg veh −1 km −1 (cobble stone).…”
Section: Outdoor Pollution Sourcesmentioning
confidence: 99%